The Gradual Advancement of Trans Rights: A Critical Perspective on the Case-law of European Supranational Courts (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This article seeks to analyze the case-law of the Court of Justice of the European Union and the European Court of Human Rights concerning legal recognition of gender identity within member states. It adopts a critical perspective, emphasizing the actual realization of fundamental human rights. The analysis will reveal that, despite notable differences, both Courts have moved away from a biologically essentialist framework, gradually progressing toward a model focused on self-determination. However, this evolution has not yet fully embraced depathologization or the complete acknowledgment of trans identities.
Keywords: Gender recognition; trans rights; EU law; ECtHR; depathologization